Penundaan Pembagian Harta Warisan Di Desa Morang Kecamatan Batang Onang Kabupaten Padang Lawas Utara Dalam Perspektif Hukum Islam - Nasution, Nur Halimah; Siregar, Fatahuddin Aziz; Hasibuan, Ahmad Soleh (Jurnal El-Thawalib, 2024)
Based on the background of the problem in this research, the community in Morang Village did not distribute inheritance after their father and mother died for certain reasons and without any deliberation from all the heirs, while postponing the distribution of inheritance could lead to huge conflicts in the future. According to Islamic law, if you want to postpone the distribution of inherited assets, you must have the consent of all the heirs. The formulation of the problem in this research is what are the factors that cause delays in the distribution of inheritance? What is the view of Islamic law regarding postponing the distribution of inherited assets? and what is the impact of postponing the distribution of inheritance? The aim of this research is to find out what factors cause delays in the distribution of inheritance, as well as how Islamic law views delays in the distribution of inheritance and to find out what the consequences of delays in the distribution of inheritance are. The theory in this research is related to the theory of understanding inheritance, the basis of inheritance law based on the Al-qu'an, the basis of inheritance law based on ijtihad, the principles of inheritance in Islamic law, the causes of inheritance, heirs and their respective parts, expert groups inheritance according to lineage, heirs generally determined in the hadith, factors hindering inheritance according to Islamic law, obligations of heirs to heirs. This research is quantitative research, namely research carried out by collecting primary data and secondary data on phenomena seen directly in the Morang Village community. The primary data source for this research is the people of Morang Village, Batang Onang District, conducting interviews and documentation. And the secondary data in this research are books, journals, theses and other supporting sources. Based on the results of this research, the researchers concluded that the delay in the distribution of inheritance was caused by economic and educational factors, customary and customary factors, and the public's lack of understanding regarding delays in the distribution of inheritance. According to Islamic law, the postponement of the distribution of inherited assets must be hastened and the distribution of inherited assets may be carried out for valid reasons and with the consent of all other heirs. The impact of postponing the distribution of inherited assets is the breakdown of relationships, changing the status of inherited property rights to personal property rights, quarrels between families and reduced harmony within the family.